# |
ODE |
Mathematica |
Maple |
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \cos \left (x \right )+\sin \left (x \right )
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+\left (-1+\cos \left (x \right )\right ) y^{\prime }+y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime \prime }+\frac {y^{\prime }}{x}+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime \prime }+\frac {y^{\prime }}{x}+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) \left (3 x -1\right ) y^{\prime \prime }+\cos \left (x \right ) y^{\prime }-3 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-x y = x^{2}+2 x
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = 1
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+\left (x -6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (3 x^{2}+2 x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3}+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3} \cos \left (x \right )+\sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} \left (x^{2}+x +1\right ) y^{\prime \prime }+x \left (11 x^{2}+11 x +9\right ) y^{\prime }+\left (7 x^{2}+10 x +6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (x +3\right ) y^{\prime \prime }+5 x \left (1+x \right ) y^{\prime }-\left (1-4 x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (-x^{2}+2\right ) y^{\prime \prime }-x \left (4 x^{2}+3\right ) y^{\prime }+\left (-2 x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = \sec \left (x \right )^{4}
\] |
✗ |
✗ |
|
\[
{}\left (y-2 x y^{\prime }\right )^{2} = {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -1\right ) y^{\prime \prime }+3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (x^{2}-2 x +1\right ) y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (x +4\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} \left (x +2\right ) y^{\prime \prime }+5 x^{2} y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x y^{\prime }+\left (x -5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = \sin \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = x^{3}+x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime \prime }+2 x y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x \right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}+6 x \right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}-8\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-9 x y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }-\left (x^{2}+\frac {5}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+4 x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }+y^{\prime }+y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (1-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+y = \frac {1}{1-x}
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+x y = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = \left (x^{2}+3\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )+2 y \left (t \right )+2 t +1, y^{\prime }\left (t \right ) = 5 x \left (t \right )+y \left (t \right )+3 t -1]
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+20 y^{\prime }+500 y = 100000 \cos \left (100 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = A y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 6 \,{\mathrm e}^{x} x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+y = \frac {1}{x^{2}}
\] |
✓ |
✗ |
|
\[
{}x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime } = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+y = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}h^{2}+\frac {2 a h}{\sqrt {1+{h^{\prime }}^{2}}} = b^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-24 y = 16-\left (x +2\right ) {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = {\mathrm e}^{a \cos \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2 y \ln \left (y\right )+y-x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+{\mathrm e}^{-y} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{\mathrm e}^{y} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+3 x -2 y+6}{x y-3 x -2 y+6}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = b y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y^{2}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x +y
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x +b y
\] |
✓ |
✓ |
|